Captain America protecting digital rights: “old school” national law vs. emerging internet complexities in Azerbaijan - Mammadrzali, Shahin (Vilnius University Open Series, 2020)
It is indicated in the article that emerging information technologies influences human rights norms in any democratic society. Especially, the Internet has changed the traditional approach to methods of ensuring human rights, while adding new challenges at the same time, such as regulating cybersecurity, digital data protection, digital freedom of information, privacy, discrimination in the Internet, etc. The traditional flow of information through newspapers, radio and television is currently combined with new means of exchanging digital information, mobile and satellite communications, the Internet and other technological advances. Of course, these innovations make governments to review traditional human rights legislation to stay fit and updated. Yet, some fundamental norms of national human rights legislation should remain unchangeable. Simply put, it looks like Captain America from the movie “Avengers” – a very old guy who develops his abilities to defeat dangers, but also preserves “old school” strength and leadership skills. In the light of these issues, the present article is devoted to the analysis of the conceptual foundations of national legislation in Azerbaijan on the protection of digital rights in the Internet. The article emphasizes that digital rights themselves are one of the factors demonstrating the strong impact of communication technologies on human rights, especially information rights and freedom of expression.